Complexidade e contradição em Álvaro Siza - Rita Senra Furtado (2015)
This dissertation aims to compare two works that we not only appreciate but have intuited to share the same point of view regarding architecture. The parallel which was built comprises the initial work of the architect Álvaro Siza, corresponding to the time period between the decades of 1950 and 1980, and the literary work written by Robert Venturi in 1966, Complexity and Contradiction in Architecture. The main purpose of this study is to unravel, in a deaper level than it has happened before, the principles underlying this hypothetic affinity that, in our opinion, will consent a 'new' perspective of both objects. If Complexity and Contradiction in Architecture represents a pivotal point of transition in terms of methodology and theory in the early work of Siza, the theorical work of Venturi gains a different pratical sense when compared with Siza's projects. The investigation is structured according to ten chapters of Complexity and Contradiction, confronting venturian examples with some of Álvaro Siza's writings and (un)built projects. In the first half of the work presented - Nonstraightforward Architecture : A Gentle Manifesto, Complexity and Contradiction versus Simplificantion and Picturesqueness, Ambiguity and Contradictory Levels - it is conceived a parallel contextual panorama that mentions themes such as the drama between the international and national styles, multidisciplinary relationships and the defense of an inclusive architecture. The second part of the study proceeds with the same topics, now seen from a methodological perspective. From the binome of order and exception addressed in the chapter Accomodation and the Limitations of Order : The Conventional Element, it is discussed Contradiction Adapted and Contradiction Juxtaposed, the Inside and the Outside, the Obligation Toward the Difficult Whole. At last, it will be advocated the existence of a comum mindset regarding both architects, based on the idea of a baroque cosmovision.